United States : Publication of Financial Sector Assessment Program Documentation; Detailed Assessment of Implementation of the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2010)
This paper presents Detailed Assessment of the United States's implementation of the International Organization of Securities Commissions' Objectives and Principles of Securities Regulation. The general preconditions for effective securities regulation in the United States are present. The legal and accounting system supports the implementation of requirements and effective regulation of market participants. The legislation regarding bankruptcy, insolvency, and winding up in the jurisdiction and the professionals associated with those matters are sophisticated.